PEMANFAATAN GEOFENCE UNTUK MENCARI LOKASI BENGKEL TAMBAL BAN TERDEKAT BERBASIS ANDROID - Wildan Azzami; Anggraini Kusumaningrum; Sudaryanto Sudaryanto (Institut Teknologi Dirgantara Adisutjipto, 2018)
The number of vehicles in Indonesia continues to increase every year. It will also be directly proportional to many people who have problems with their vehicles, such as finding a tire leaking from a nail puncture or other causes. And will also increase the need for tire services. For vehicle users who do not know the area around when experiencing leak tire disaster, then directly proportional to search for the nearest tire repair shop will be difficult. Therefore, in this study developed information media in the form of Android-based applications to map the locations - workshop tire repair shop, as well as search for the nearest tire patch based on the location of the rider by using geofence system, where in this application the user will be notified the nearest workshop with a blink on the animated image tire repairs. From the test results, this application is able to help users search for the nearest tire repair shop along with the distance from the user location. This application is also able to show related information as well as showing the distance and route of the road that will be taken from the location of the user with the location of the intended tire patch by utilizing google maps applications. Applications have been tested by questionnaire method distributed to 30 respondents with 10 questions and the results of the questionnaire calculated using the likert scale get 76,2% results and included in either category